Old technologies in a modern communications landscape: public call boxes and universal service - Jason Whalley; Volker Stocker (International Telecommunications Society (ITS), 2023)
This paper explores the changing nature of universal service. In particular, it looks at universal service obligations within the United Kingdom and the role that public call boxes play within the context of a vibrant mobile telecommunications market with extensive geographical coverage and widespread usage. Our analysis draws on data from the 2021consultation by Ofcom into the scope of the UK's universal service obligations to highlight their complex nature. Although the number of public call boxes has dramatically fallen in recent years, not least because of the growth in mobile phone usage, they still perform a vital socio-economic role. This role complicates their replacement, creating economic inefficiency but social value. The latter limits the ability of stakeholders - regulators and mobile operators - to radically amend how the universal service obligation is provided.
Keywords: 330; Public call boxes; universal service obligations; consultation; UK